From Local Wisdom to School Innovation: Reconstructing Buton Cultural Values for Character Education Management in Secondary Schools - Nanik Hindaryatiningsih; Jafar Ahiri; Omasrianto Omasrianto; Fina Amalia Masri; Ansor Putra; Jamal Harimudin (Journal of Innovation in Educational and Cultural Research, 2026)
The increasing concern about the decline in students' moral behavior has prompted the need for innovative approaches to character education, one of which is through the integration of local cultural valuesinto educational management. However, previous research has been dominated by descriptive explorations of local wisdom and has yet to yield systematic integration into the school management framework. This study aims to reconstructButonesecultural values into an innovative model for character education management in secondary schools. This study uses a qualitative, ethnographic approach with 100 participants, including traditional leaders, community leaders, principals, teachers, and community members. Data were collected through in-depth interviews, participant observation, and document analysis, then analyzed using interactive qualitative analysis techniques. The research results identified threeButonesecultural values as the main local wisdom value concepts:gauandpombala,poromuindaposaangupogaaindakoolota, andtuturakanasara. These three cultural values appear across four organizational management systems in educational institutions. Quantitatively, the implementation function shows the highest percentage at 31%, followed by evaluation at 29%, organizing at 22%, and planning at 18%, indicating the dominance of implementing cultural values in educational practices. The character values found in theButoneselocal culture include responsibility (58%), cooperation (55%), empathy (40%), discipline (57%), and integrity (33%). Qualitatively, these findings illustrate the integration of local wisdom values in school management to strengthen the implementation of character education programs. Students have a higher level of social awareness and a greater sense of responsibility for maintaining local culture. Thus, this research contributes to the literature on innovative, contextually responsive culture-based education management. The local wisdom valuesare developed into contemporary character education concepts.